2021
DOI: 10.3390/brainsci11050651
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Demographical and Clinical Indices of Patients with Chronic Disorders of Consciousness

Abstract: This work aims to evaluate the prognostic value of the demographical and clinical data on long-term outcomes (up to 12 months) in patients with severe acquired brain injury with vegetative state/unresponsive wakefulness syndrome (VS/UWS/UWS) or a minimally conscious state (MCS). Patients (n = 211) with VS/UWS/UWS (n = 123) and MCS (n = 88) were admitted to the Federal Research and Clinical Center of Intensive Care Medicine and Rehabilitology after anoxic brain injury (n = 53), vascular lesions (n = 59), trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…(H) The changes in amplitude of N20 on both side between the three groups were statistically significant. (Xie et al, 2011;Liu et al, 2016) demonstrated that rTMS can significantly increase regional cerebral blood flow and cerebral blood velocity in patients with pDOC, and Zhang et al (2021) found that rTMS can improve the excitability of the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(H) The changes in amplitude of N20 on both side between the three groups were statistically significant. (Xie et al, 2011;Liu et al, 2016) demonstrated that rTMS can significantly increase regional cerebral blood flow and cerebral blood velocity in patients with pDOC, and Zhang et al (2021) found that rTMS can improve the excitability of the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…DOC always leads to severe complications, including but not limited to pneumonia, digestive tract hemorrhage, and liver dysfunction, poor clinical outcomes, and high mortality rates. Within a year after experiencing DOC, 35% of patients will die, and only 40% will experience an improved level of consciousness ( Nekrasova et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main etiology of the VS/MCS in this study was non-traumatic, which has been shown to have a worse prognosis in terms of survival and neurological recovery according to many longitudinal studies. 16 , 17 Our study included only ventilated patients who may have had a worse prognosis and more severe brain injury than non-ventilated patients. However, other studies such as the study by Estraneo et al 18 did not demonstrate the association between etiology and prognosis in patients with VS/MCS.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely, as they have been grouped with other patients in studies of long-term recovery, that mixed vascular cDOC patients may be able to recover consciousness past 3 months. 62 One study with 1-year follow-up of 211 patients found that 23.5% of vascular pDOC patients were able to recover communication by 3 months, which was higher than AIE but lower than TBI patients. 62 However, vascular DOC patients had a 40.7% mortality rate over the first year after injury, similar to AIE DOC.…”
Section: Prognosis By Etiologymentioning
confidence: 98%